Recent Advances in Inorganic Chiral Nanomaterials. Issue 50 (17th February 2021) - Liu, Junjun; Yang, Lin; Qin, Ping; Zhang, Shiqing; Yung, Ken Kin Lam; Huang, Zhifeng
Abstract: Inorganic nanoparticles offer a multifunctional platform for biomedical applications in drug delivery, biosensing, bioimaging, disease diagnosis, screening, and therapies. Homochirality prevalently exists in biological systems composed of asymmetric biochemical activities and processes, so biomedical applications essentially favor the usage of inorganic chiral nanomaterials, which have been widely studied in the past two decades. Here, the latest investigations are summarized including the characterization of 3D stereochirality, the bionic fabrication of hierarchical chirality, extension of the compositional space to poly‐elements, studying optical activities with the (sub‐)single‐particle resolution, and the experimental demonstration in biomedical applications. These advanced studies pave the way toward fully understanding the two important chiral effects (i.e., the chiroptical and enantioselective effects), and prospectively promote the flexible design and fabrication of inorganic chiral nanoparticles with engineerable functionalities to solve diverse practical problems closely associated with environment and public health. Abstract : Imposing chirality onto inorganic nanomaterials is essentially required for developing prominent biomedical applications intrinsically associated with homochirality, as well as for advanced light polarization. Recent investigations in inorganic chiral nanomaterials are summarized, paving the way to fully understanding the important chiral effects and prospectively exploring diverse applications with enhanced functionalities.